Advances in Regulatory Strategies of Differentiating Stem Cells towards Keratocytes - Aini Zhang; Wei Zhang; Ludvig J. Backman; Jialin Chen (Stem Cells International)
Corneal injury is a commonly encountered clinical problem which led to vision loss and impairment that affects millions of people worldwide. Currently, the available treatment in clinical practice is corneal transplantation, which is limited by the accessibility of donors. Corneal tissue engineering appears to be a promising alternative for corneal repair. However, current experimental strategies of corneal tissue engineering are insufficient due to inadequate differentiation of stem cell into keratocytes and thus cannot be applied in clinical practice. In this review, we aim to clarify the role and effectiveness of both biochemical factors, physical regulation, and the combination of both to induce stem cells to differentiate into keratocytes. We will also propose novel perspectives of differentiation strategy that may help to improve the efficiency of corneal tissue engineering.